Peliputan Isu Lingkungan dan Pembangunan Berkelanjutan - Alex Sobur (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
The press role, in order to support development process, is undeniable. Such was the case of environmental issue when the news of possible environmental damage appeared as importantreports in the newspaper. Over the last 35 years, environmental issues has moved from periphery to central of state policy—thanks to the press who consistently reported and develop a kind of environmental journalism. This article describes characteristics of environmental report which concentrated more on the cause instead of effect.